Next‐generation monitoring in obstetrics: Assessing the accuracy of non‐piezo portable ultrasound technology - Ruben Plöger; Charlotte Behning; Adeline Walter; Jorge Jimenez Cruz; Ulrich Gembruch; Brigitte Strizek; Florian Recker (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The emergence of handheld ultrasound devices capable of connecting to cell phones or tablets heralds a significant advancement in medical technology, particularly within the field of obstetrics. These devices offer the promise of immediate bedside ultrasound examinations, potentially revolutionizing patient care by enabling fetal assessments in diverse settings. Material and Methods This prospective study aimed to validate the reliability of non‐piezo, chip‐based handheld ultrasound devices in clinical obstetric practice. Conducted in a university hospital obstetric ward, the study included 100 pregnant women between 17 and 41 weeks of gestation. Participants underwent ultrasound examinations using both conventional and portable point‐of‐care ultrasound (POCUS) devices to compare the accuracy in estimating fetal weight and other parameters, such as cardiac activity, fetal presentation, placental location, and amniotic fluid volume. The reliability and agreement between the devices were assessed using intraclass correlation coefficients, Bland–Altman plots, and Pearson correlation coefficients. Results The results show a near‐perfect agreement (0.98) and correlation (r = 0.98, p < 0.001) for estimated fetal weight and most biometry measurements between the two types of ultrasound devices, with slight deviations in head circumference and amniotic fluid index measurements. Subgroup analysis revealed variations in agreement and correlation rates with higher BMI and advanced gestational age, indicating areas for further refinement. Conclusions These findings affirm the high reliability of handheld ultrasound devices for basic obstetric ultrasound evaluations, supporting their integration into daily clinical practice. This technology improves the flexibility and immediacy of prenatal care, although further research is needed to optimize its application across patient populations and treatment settings.